Pap test: evaluation of quality of cervical smears - Flávia Andréia Pereira Soares dos Santos; Rosineide Santana de Brito; Danyelle Leonette Araújo dos Santos (Rev Rene)
The study aimed to evaluate the quality of the cervical smear test to prevent cervical cancer executed in Basic Health Units, based on the criterion of the Brazilian Nomenclature for Reporting Cervical Brazilian and procedures recommended. 134 Pap test results, realized from February to May 2009 in three Basic Health Units in a town of Rio Grande do Norte, Natal-Brazil, were selected. Of these, 107 had the representation of squamous and glandular epithelia and/or metaplastic, and 27 did not show the squamocolumnar junction. This was deemed alarming because of the possibility of exposing women to a false negative result, putting it at risk to health. Realized the need for monitoring, supervision and evaluation of activities related to disease prevention, seeking to ensure the quality of results and thus to indicate ways to improve the service and attention to the health of the female population.